Stereoselective Allyl Enol Carbonates for the Synthesis of Chiral Aldehydes Bearing All Carbon Quaternary Stereocenters via the Decarboxylative Asymmetric Allylic Alkylation (DAAA) - Alberch, Eduardo; Brook, Colin; Asad, Sharif A.; Shevyrev, Maria; Ulicki, Joseph S.; Hossain, M. Mahmun (Synlett, 2015)
A stereoselective synthesis of carbonates derived from 3-hydroxy-2-aryl acrylates was devised that can form the Z- or E-stereoisomer in very high Z/E ratios (50:1 and 1:99, respectively). The stereochemical outcome depends on the choice of base, addition of TMEDA and reaction temperature. The Z- and E-stereoisomers have different reactivities towards the DAAA reaction, with the E-stereoisomer displaying both greater reactivity and enantiodifferentiation with chiral ligands. The DAAA of E-stereoisomer analogues takes place in excellent yields ranging from 96–99% and enantioselectivities ranging from 42–78% ee.
Keywords: stereoselective synthesis; asymmetric catalysis; palladium; aldehydes; solvent effect